Korelasi Ekspresi CD47 terhadap Faktor-Faktor Klinikopatologi pada Karsinoma Ovarium: - - Fitrianti, Fitrianti; Maulani, Heni; Aspitriani, Aspitriani (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Ovarian carcinoma is the fourth most common cause of death in gynecological malignancies. CD47 is asurface protein widely expressed on many benign and malignant cells, including ovarian carcinoma. This study wasaimed to identifythe correlation between CD47 expression with clinicopathological factors inovarian carcinoma.Case series studies was undertaken started on January 1, 2016 to October 31, 2019 at Department of Anatomic Pathology Faculty of Medicine Sriwijaya University/Mohammad Hoesin Hospital, Palembang. Fifty cases, consisting of LGSC, HGSC, MC, EC, CCC, each 10 cases were selected. The slides were stained with anti-CD47 antibody. The correlation of expression of anti CD47 protein with ages, clinical stages and CA125 serumwere analysed byGamma test. The correlation of expression of anti CD47 protein with histopathologic subtypes and chemotherapeuticresponses were analyzed using Contingency test.There was no significantcorrelation between CD47 expression with ages (p=0.130), histopathological subtypes (p=0,956), FIGO clinical stages (p=0.459), CA125 serum level (p=0.366) and chemotherapeutic response (p=0.129).Althoughthere was no significant correlation between CD47 expression and clinicopathological characteristics,atendency that the higher expression CD47 will be followed by the younger age groups, higher clinical stagesand higher CA125 serum was observed.